El cuento infantil en el desarrollo emocional: una estrategia pedagógica - Chela Guambuguete,Jessica Abigail (2025)
Children's stories stand out as an essential pedagogical tool in early childhood education, as they contribute to both the emotional and cognitive development of children. Their use in the classroom allows for a broader focus of attention, improved concentration and strengthened memory, as well as stimulating curiosity and imagination. Through narrative, children not only develop their understanding of the world, but also fundamental emotional skills, such as empathy and emotion regulation. By identifying with the characters and their experiences, children learn to manage their emotions and understand others, which fosters healthy relationships and better social adaptation. Likewise, stories help children follow logical sequences, foresee consequences and solve problems, complex skills that facilitate their reasoning. However, many teachers lack the adequate resources to effectively implement this strategy, given that the traditional educational approach usually prioritizes cognitive learning over socio-emotional learning. The proposed objective is to analyze the use of children's stories as a pedagogical strategy and emotional development in children. Hence the importance of integrating the story as a strategic pedagogical tool that promotes comprehensive learning and creates an empathetic and inclusive teaching environment. Finally, the story is a powerful way to nurture both emotional development and interest in reading in children, facilitating their personal growth and adaptation to society